Seston fluxes in the dam of a Colombian tropical reservoir (2010)
ABSTRACT: Aim: Quantify sedimentation rates in Rio Grande II reservoir, his temporal fluctuation, and the degree of mineralization of the material that reaches the sediment; Methods: A system of five sedimentation traps was used to evaluate temporal variability of seston flux and the total sedimentation in the dam of Río Grande II reservoir AntioquiaColombia (6° 32, 62’ N, 75° 27, 27’ W); Results: The flux total solids presented a mean value of 4540 g.m-2.d-1 with a range oscillating between 229 and 18573 g.m-2.d-1, being the fixed and suspended fraction the most of the total solids. It was evidenced that the largest fluxes were presented between the fourth and the fifth trap (the nearest to the bottom) due to hypolimnetic fluxes which contain materials of the tributaries and resuspended material. The first three traps collected particles that settled from the column of water without evaluate the overtrapping for resuspension. In some samplings the mineralization between the third and fourth trap was maximum (100%). The fluxes of seston particles presented a mean value of 3554 g.m-2.d-1 with a range between 810 and 18955 g.m-2.d-1, being predominant the inorganic fraction; Conclusions: The seston is mainly of allochthonous origin and variated in the time and in the vertical level. There was not found a significant relationship between level of the reservoir and the mixing depth with the fluxes of total sedimentation and seston; however there was relation between seston concentration and wind speed.